Reading time : the literate lives of urban secondary students and their families - Compton-Lilly, Catherine (New York ; London : Teachers College Press, Teachers College, Columbia University, 2012)
Catherine Compton-Lilly examines the literacy practices and school trajectories of eight middle school students and their families. Through a unique longitudinal lens--the author has studied these same students from first grade--we see how students from a low-income, inner-city community grow and develop academically, revealing critical insights for teachers about literacy development, identity construction, and school achievement. --from publisher description
Introducing time -- Time, theory, and Javon -- Time and change -- Students, reading, and books -- Teaching and time -- Parents' voices: memories and making sense -- Thinking about the future, drawing upon the past, and living in the present -- Time and literacy practices: becoming a reader over time -- Conclusion: reading time.
Includes bibliographical references (pages 132-138) and index.
Keywords: Urban youth -- Education -- United States -- Case studies; Urban youth -- Books and reading -- United States -- Case studies; Middle school students -- Books and reading -- United States -- Case studies; Reading -- Parent participation -- United States -- Case studies; Education, Urban -- United States -- Case studies